Desconcentraç\~ao territorial e reestruturaç\~ao regressiva da indústria no Brasil: Padr\~oes e ritmos - Aristides Monteiro Neto; Raphael de Oliveira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper aims to investigate structural transformations in Brazilian regional disparities. It puts focus on concentration/deconcentration movements presented in the industrial activities. It examines reasons why industrial sector has been moving from the state of S\~ao Paulo to other regions in Brazil, particularly, to the South. Special results were shown and they say that deconcentration continues to occur in the 1996-2015 period. However, the most prominent industrial activities related to higher aggregate values and productivity levels remain located in high-developed areas.
Keywords: O14; O33; R11; R12; 330; industrial restructuring; regional development; deindustrialization